2021
DOI: 10.3389/fmicb.2021.771805
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Co-infection With Fowl Adenovirus Serotype 4 and 8a

Abstract: Fowl adenoviruses (FAdVs), which are distributed worldwide, have caused considerable economic losses to poultry farms. Co-infection with FAdVs and other avian pathogens has been reported previously. However, the pathogenicity of different serotypes of FAdVs causing co-infection remains unclear. Herein, strain HN from FAdV species C serotype 4 (FAdV-4) and strain AH720 from species E serotype 8a (FAdV-8a) were used to assess the pathogenicity of their co-infection in specific-pathogen-free (SPF) chickens. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Moreover, pulmonary histopathological lesions characterized by congestion of numerous blood vessels and acute bronchopneumonia similar results were documented by [ 44 ] who detected that structural disorder of the pulmonary bronchus, inflammatory exudation, and alveolar rupture in infected birds.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, pulmonary histopathological lesions characterized by congestion of numerous blood vessels and acute bronchopneumonia similar results were documented by [ 44 ] who detected that structural disorder of the pulmonary bronchus, inflammatory exudation, and alveolar rupture in infected birds.…”
Section: Discussionsupporting
confidence: 83%
“…Finally, this study concentrated on the fowl adenovirus infections only, even though concurrent diseases have been reported (Toro et al, 2000;Mei et al, 2020). It is also important to note that simultaneous infections with multiple strains of fowl adenovirus can enhance the viral replication capacity of strains and increase the viral load (Liu et al, 2021). Notwithstanding, the outcomes of this study may provide valuable information for the further investigation of the fowl adenoviruses in the same geography.…”
Section: Various Methods Have Been Proposed To Detectmentioning
confidence: 94%
“…On the other hand, the birds analyzed in this study were not vaccinated, so it can be deduced that the viral strains that are present in commercial batches are field strains. Many studies showed that the genotypes characterized here were associated with outbreaks of IBH or HHS in chickens in several countries around the world [ 41 , 46 , 47 , 48 ]; however, the vast majority of reports of IBH or HHS worldwide have been associated with FAdV-4/C1 [ 23 , 49 , 50 , 51 , 52 ] and the report of a large number of outbreaks associated with this FAdV genotype has led many studies to focus on the development of vaccines based on this viral genotype [ 53 , 54 , 55 ], as well as associations with other genotypes (FAdV-8b/E3) where excellent protection against infections with both genotypes is shown [ 1 , 12 , 56 , 57 , 58 ]. However, these recombinant vaccines have not been tested with other FAdV genotypes that are included in the same group to which the vaccine strains belong, in the case of FAdV-8b/E3 belonging to species E, perhaps it could generate protection against FAdV-8a/E2 and FAdV-6/E1 strains and be an alternative in the country.…”
Section: Discussionmentioning
confidence: 99%